2020
DOI: 10.1016/j.jid.2019.05.024
|View full text |Cite
|
Sign up to set email alerts
|

IL-4Rα Blockade by Dupilumab Decreases Staphylococcus aureus Colonization and Increases Microbial Diversity in Atopic Dermatitis

Abstract: Dupilumab is a fully human antibody to interleukin-4 receptor a that improves the signs and symptoms of moderate to severe atopic dermatitis (AD). To determine the effects of dupilumab on Staphylococcus aureus colonization and microbial diversity on the skin, bacterial DNA was analyzed from swabs collected from lesional and nonlesional skin in a double-blind, placebo-controlled study of 54 patients with moderate to severe AD randomized (1:1) and treated with either dupilumab (200 mg weekly) or placebo for 16 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
162
1
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(187 citation statements)
references
References 57 publications
11
162
1
13
Order By: Relevance
“…Previous studies show an effect of medication use on the skin microbiome. However, it was not possible to discontinue medication use in this group of patients with difficult to treat, moderate to severe disease . During this study, the use of medication was carefully monitored and showed no significant differences between both treatment groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies show an effect of medication use on the skin microbiome. However, it was not possible to discontinue medication use in this group of patients with difficult to treat, moderate to severe disease . During this study, the use of medication was carefully monitored and showed no significant differences between both treatment groups.…”
Section: Discussionmentioning
confidence: 86%
“…However, it was not possible to discontinue medication use in this group of patients with difficult to treat, moderate to severe disease. 8,45 During this study, the use of medication was carefully monitored and showed no significant differences between both treatment groups. Results for patients using systemic medication at T0 did not deviate from the rest of the study population (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…It has been confirmed to be effective in patients with moderate to severe AD in several double-blind, placebocontrolled studies and in clinical practice [43][44][45]. The result showed that clinical improvement is positively correlated with increased favorable microbial community and reduced abundance of S. aureus [46]. More novel systemic immunomodulatory agents for AD are under development, and it is promising that these therapies will not only improve skin immunity but also adjust S. aureus colonization by modulating their cell wall proteins [19].…”
Section: Biological Therapy In Patients With Admentioning
confidence: 87%
“…Moreover, recent studies have shown S aureus levels to decrease during treatment of AD and to rebound after the end of treatment in some but not all patients. 8,9 Furthermore, we now have a better understanding of the mechanism behind the interaction between S aureus and other bacterial species, the skin barrier, and immune dysregulation in patients with AD. 10 Thus skin microbiome measurement of S aureus, notably a noninvasive procedure, might become a clinical biomarker for treatment success, most importantly indicating a sustained microbial response (SMR) that will allow determination of optimal treatment duration ( Fig 1).…”
Section: Promises: Biomarker For Ad Severity and Personalized Treatmentmentioning
confidence: 99%